Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1121/1.1783352
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chinese tone recognition by manipulating amplitude envelope: Implications for cochlear implants

Abstract: Tone recognition is important for speech understanding in tonal languages such as Mandarin Chinese. Cochlear implant patients are able to perceive some tonal information by using temporal cues such as periodicity-related amplitude fluctuations and similarities between the fundamental frequency (F0) contour and the amplitude envelope. The present study investigates whether modifying the amplitude envelope to better resemble the F0 contour can further improve tone recognition in multichannel cochlear implants. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 17 publications
4
62
0
Order By: Relevance
“…Xu et al (2002) also found that, as in English phoneme recognition, there was a tradeoff between the temporal and spectral cues for lexical tone recognition. Efforts aimed at enhancing the temporal envelope cues for tone recognition or pitch perception using acoustic simulations or actual cochlear implants have yielded only modest success (e.g., Geurts and Wouters, 2001;Green et al, 2004Green et al, , 2005Hamilton et al, 2007;Laneau et al, 2006;Luo and Fu, 2004;Vandali et al, 2005Vandali et al, , 2007. On the other hand, few studies have attempted to manipulate the spectral cues to improve tone recognition or pitch perception (e.g., Geurts and Wouters, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2002) also found that, as in English phoneme recognition, there was a tradeoff between the temporal and spectral cues for lexical tone recognition. Efforts aimed at enhancing the temporal envelope cues for tone recognition or pitch perception using acoustic simulations or actual cochlear implants have yielded only modest success (e.g., Geurts and Wouters, 2001;Green et al, 2004Green et al, , 2005Hamilton et al, 2007;Laneau et al, 2006;Luo and Fu, 2004;Vandali et al, 2005Vandali et al, , 2007. On the other hand, few studies have attempted to manipulate the spectral cues to improve tone recognition or pitch perception (e.g., Geurts and Wouters, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, less-thanresolute representations of F0s is a problem for implants, and this problem has received considerable attention (e.g., Wouters, 2001, 2004;Luo and Fu, 2004;Green et al, 2005;Laneau et al, 2006;Carroll and Zeng, 2007;Chatterjee and Peng, 2007;Sucher and McDermott, 2007). Unfortunately, a way to improve the representations has not been identified to date despite these efforts.…”
Section: Less-than-resolute Representations Of Fundamental Frequenciementioning
confidence: 99%
“…Different semitone spacing and intensity changes between successive notes were used to vary the perceptual salience of pitch and loudness cues, respectively, as the integration of both cues may depend on their relative salience. Previously, we have found that CI users' Mandarin tone recognition was enhanced when the amplitude envelope was modified to follow the pitch contour of lexical tone (Luo and Fu, 2004). In this study, CI users' contour identification is hypothesized to be better when pitch and loudness cues are consistent.…”
Section: Introductionmentioning
confidence: 95%